MENYELIDIKI SEJARAH DESA SAKERTA TIMUR SEBAGAI DESTINASI WISATA POPULER DI JAWA BARAT - Santi Maudiarti; Hanni Adriani (Akademika, 2021)
The tourism industry is one of the primary needs for the life of modern society today. Because of these factors, it makes the need for recreation or tourism increases. East Sakerta Tourism Village is one of the leading tourist destinations in the Kuningan Regency. This village has a long history and interesting community culture, but not many people know about it. This study aims to investigate the history of the East Sakerta Village as a popular tourist destination in West Java. The research method used is a qualitative method. This data collection method is carried out using the Focus Group Discussion (FGD) method. Primary data collection was carried out directly and purposive sampling by interviewing key people, namely the village government apparatus, tourism community leaders (kompepar), and the community. FGD method was used to find out about the history, legends, and culture of the East Sakerta Village. The results of FGD findings consist of the religion, the history of the village, the local culture, the historical sites, the myths and legend, and the philosophy of Sakerta Timur Village. The philosophy concept is "Tumaritis" which is a village in the Sundanese and Javanese puppet which has a philosophy of mutual protection, security, and prosperity.